The mysterious case of theory and practice: crime fiction in collaborative translation - Maher, Brigid (The Journal of Specialised Translation, 2014)
This article focuses on the process of collectively translating a short text by Carlo Lucarelli, a prominent Italian crime writer. Lucarelli's novels explore a range of problems affecting contemporary Italian society, including corruption, state violence and organised crime. Consequently they are deeply rooted in their culture of origin, while also fitting into a recognisable globalised genre. This makes Lucarelli's writing a challenge to translate while also, potentially, making it quite marketable in translation, since it can hold considerable appeal for overseas audiences. I reflect on the translation challenges from both theoretical and practical perspectives. The practical angle is based on my experience leading a group of translators, together with Lucarelli himself, at the 2013 Translation Winter School, dedicated to crime fiction, in Melbourne. Over a number of days, workshop participants prepared a consensus translation of an excerpt of Lucarelli's work, exploring practical solutions to questions of intertextuality, genre, audience expectations and culture-specific references. By analysing the process of experimentation and debate that group translation sets off, I investigate the crucial but sometimes neglected interaction that can take place between theory and practice as a piece of Italian crime fiction is reworked for an Anglophone (even Australian) audience. I also explore the many benefits of collaborative translation.